Hydrolases - Haider, Sajjad; Haider, Adnan; Catalá, Angel (Biochemistry, 2022)
This book gives a current review of the links between the structure and function of hydrolases and ligases, as well as ideas for better using these critical enzymes. The book is split into two sections: "Cleavage" and "Ligases." These enzymes are the biggest and most varied family of enzymes, allowing researchers to investigate the structural variety that underpins their different biological roles. In light of recent scientific advances, there is a desire to examine and update our knowledge of these enzymes' functional and structural changes.